ALGORITHM FOR DATA FLOW CONTROL ON THE CORPORATE PORTAL - Orazbekov Ж. Н.; Moshkalov А. Қ; Sharmukhanbet С.Р.; Sabraev Қ. Ж. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
Currently, despite the large number of developments in this area, it is very difficult to say which algorithm is used in real networks. This is due, firstly, to the lack of universality of the algorithms, that is, the similarity of performance regardless of the type of traffic and network types, for example, depending on the power consumption or channel occupancy, delay in the queue, and the size of the router. Secondly, the complexity of tuning the parameters of the algorithm, which works well in all possible cases. To use bandwidth efficiently, you must select the most efficient queue management algorithm that provides the most efficient network service and maximum resource utilization. The article describes the main mechanisms for quality assurance, the principles of queue management algorithms and modeling skills, topological modeling, channels and media components for transferring production data in the form of basic topological objects in the model, an effective queue management algorithm in a corporate environment. data processing and exchange.